2021
DOI: 10.1136/jitc-2020-001719
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of thromboembolism in patients with melanoma on immune checkpoint inhibitor therapy and its adverse association with survival

Abstract: BackgroundThromboembolism (TE) in cancer significantly contributes to morbidity and mortality. Little is known about the incidence of arterial TE (ATE) and venous TE (VTE) in patients with melanoma on immune checkpoint inhibitor (ICI) therapy.MethodsWe conducted a retrospective cohort study of patients with melanoma receiving ICI from July 2015 through December 2017 at the Cleveland Clinic. TE, including VTE events of deep venous thrombosis, pulmonary embolism, visceral vein thrombosis, and ATE events of myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 52 publications
6
82
1
Order By: Relevance
“…However, our data are consistent with previous studies and randomized phase III trials [32], which found no association of concomitant AC with prolonged survival in patients with NSCLC [16] or other advanced solid cancer entities [19,21]. Although the cancer-specific risk of VTE in the pre-ICI era was found to be smaller in melanoma patients [33], melanoma patients treated with ICI show similar rates of TEE-and VTE-associated mortality as compared to patients with other advanced cancers [27,34,35], providing a biological rationale for AC therapy [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, our data are consistent with previous studies and randomized phase III trials [32], which found no association of concomitant AC with prolonged survival in patients with NSCLC [16] or other advanced solid cancer entities [19,21]. Although the cancer-specific risk of VTE in the pre-ICI era was found to be smaller in melanoma patients [33], melanoma patients treated with ICI show similar rates of TEE-and VTE-associated mortality as compared to patients with other advanced cancers [27,34,35], providing a biological rationale for AC therapy [21].…”
Section: Discussionsupporting
confidence: 92%
“…However, given the strong heterogeneity of patients in terms of the primary tumor localization, the question as to whether the use of AC in general and the application of FXa or thrombin inhibitors more specifically might impact the outcome of ICI treatment might be better addressed in defined tumor entities with unmet clinical needs in improvements of ICI therapy. The exigency to comprehensively analyze the clinical wirings between the use of (different) anticoagulants and ICI in patients with advanced melanoma is highlighted when taking into account the increased risk of thromboembolic events (TEE) in patients treated with ICI and the TEE-associated adverse survival [21].…”
Section: Introductionmentioning
confidence: 99%
“…The references in the relevant articles were also manually searched for related studies. Overall, 18 retrospective studies reporting incidences and/or outcomes of venous and/or arterial thrombosis in patients on ICIs [ 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and 4 additional relevant systematic reviews and meta-analyses [ 24 , 25 , 26 , 27 ] were identified and included in this review.…”
Section: Methodsmentioning
confidence: 99%
“…In patients receiving ICIs, several studies have shown that the occurrence of thrombosis was associated with worsening survival [10,11,[20][21][22] while others have not [14][15][16] (Table 2). Possible explanations of worse survival in patients who developed VTE include that thrombosis is an indicator for more advanced cancer stage, worse prognosis, poorer performance status, and/or thrombosis or anticoagulation-related mortality.…”
Section: Survival and Thrombosis In Patients Receiving Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Pulmonary embolism (PE) is more common in melanoma patients treated with ICIs (Sussman et al, 2021). Furthermore, it appears to be more prevalent in patients treated with combination checkpoint inhibition in comparison with single-agent therapy.…”
Section: Acute Immune Checkpoint Inhibitor-mediated Pulmonary Emergenciesmentioning
confidence: 99%